Analysis of Coastal Community Empowerment in Caring for the Environment (Case Study in the Port of Bandar Sri Setia Raja (BSSR) Selatbaru in District Bantan). (Jurnal Kajian Lingkungan, 2013)
The importance of the port as a liaison between the islands terminal carrying passengers and goods can not be denied as the presence of the Port of Bandar Sri Setia Raja (BSSR) Selatbaru in Bantan District, Bengkalis District, Riau Province. In order for this port assets can be maintained properly and make it as one of the public in obtaining alternative employment or income generation, efforts to preserve the environment around the port needs to get the attention of the people who supported of human capital (human capital), social capital (social capital) and government support.Formulation of the problem in this study is: "What factors are affecting the level of empowerment in preserving the environment around Port BSSR Selatbaru in District Bantan? "The purpose of this study was to analyze whether the factors that influence the level of empowerment of communities in conserving the environment around Port BSSR Selatbaru in District Bantan. The hypotheses are: 1). The influence of human capital (X1), social capital (X2), government support (X3) on the level of empowerment (Y1) in conserving the environment (Y2) partially and simultaneously, 2). The influence of the level of empowerment (Y1) in conserving the environment (Y2) simultaneously.Based on the results obtained as follows: (1). Human capital (X1) has the effect of very low or very weakly on the level of empowerment (Y1) of 0.016. (2). Social capital (X2) has no effect on the level of empowerment (Y1) of - 0.251. (3). Government support (X3) has the effect of very high or very strong on the level of empowerment (Y1) of 0.979. (4). Human capital (X1) has the effect of very low or very weak for environmental protection (Y2) of 0.042. (5). Social capital (X2) has no effect on the preservation of the environment (Y2) of - 0.198. (6). Government support (X3) has a high or powerful influence on environmental preservation (Y2) of 0.806. (7). Influence the level of community development and environmental conservation of - 3.045. (8). The influence of human capital, social capital and government support for community empowerment levels together (synchronously or simultaneously) is significant where F count (1916.45)> F table (2,70). (9). The influence of human capital, social capital and government support for environmental protection jointly (synchronously or simultaneously) is significant where F count (70.165)> F table (2.70), (10). The first substructure regression equation Y1 = 0.016 X1 - 0.251 X2 + 0.979 X3 + 1.6%, (11). The secondAnalisis Tingkat Pemberdayaan Masyarakat PesisirDalam Menjaga Kelestarian Lingkungan Hidup (KasusDi Pelabuhan Bandar Sri Setia Raja (Bssr) Selat Baru Di Kecamatan Bantan)Â©2013 Pusat Penelitian Lingkungan Hidup Universitas Riau 177substructure regression equation is: Y2 = 0.042 X1 - 0.198 X2 + 0.806 X3 - Y1 + 3,045 31.3%.Keywords: Coastal Community Empowerment, Caring for the Environment, Human Capital, Social Capital, Government Support